Pendampingan Belajar Melalui Media Ajar QuizWhizzer Terkait dengan Respons Peserta Didik MTs Negeri Kota Batu - Natia, Syarifah Ainur; Sitti Nur Alisyah Saputri; Fitriani Nur; Rachmah Ratnaningtiyas; Nursalam, Nursalam (Universitas Methodist Indonesia, 2024)
Education is a fundamental element in developing individual potential, especially in the Society 5.0 era, which is characterized by advances in information technology. The learning motivation of students in class VIII C at MTs Negeri Kota Batu tends to be low, which is caused by conventional learning methods that are less varied. The use of monotonous teaching media, such as WordWall, which is used repeatedly, makes students feel bored and less actively involved in the learning process. Therefore, interactive learning media such as QuizWhizzer are proposed as an innovative solution to increase the variety of learning methods and stimulate learners' interest in learning. This study aims to evaluate the effectiveness of learning assistance through QuizWhizzer teaching media related to learners' responses. The method used in this study is learning assistance, which consists of three stages: preparation, implementation, and evaluation. The results showed that the use of QuizWhizzer in learning assistance succeeded in increasing learners' positive responses by 80%, which reflected increased participation and motivation to learn. Thus, QuizWhizzer is recommended as an effective teaching medium in creating a more engaging and participatory learning environment.